Genetic gain in apomictic species of the genus Paspalum - Emerson André Pereira; Miguel Dall’Agnol; Karla Médici Saraiva; Carine Simioni; Ana Paula Steiner Leães; José Antonio Gonzalez da Silva (Revista Ceres)
ABSTRACT The objective of this work was to provide means to obtain genetic gain in apomictic species of the genus Paspalum by identifying traits that simultaneously show high correlation and heritability. Thus, to determine the amount of phenotypic variation due to genetic and environmental effects and the degree of association between leaf dry matter production and other traits of forage interest that are easy to select and measure will bring agility and economy in the selection of forage species. The experiment was conducted in the years 2009/10 and 2010/11 in the municipalities of Eldorado do Sul and Augusto Pestana, RS, Brazil, in a randomized complete block design with three replicates. The increase in the direct selection pressure on total and leaf dry matter of apomictic accesses of the genus Paspalum is enhanced by a greater contribution of genetic effects than environmental effects on the composition of the phenotypic variance. Efficient genetic gain in leaf production is achieved by indirect selection of total dry matter, which is a trait of high heritability and easy to select and measure.